Can analysis of drain fluid biomarkers predict anastomotic leak? - Jaju, Pradeep; Vallabha, Tejaswini; Kulloli, Girish; Sindagikar, Vikram (International Surgery Journal, 2021)
Background: Anastomotic leak is a major complication often leading to significant morbidity and mortality. A method to predict leaks in the early postoperative period will help in better management and outcome. Though serum biomarkers like C-reactive protein and procalcitonin levels are often used to predict chances of developing complications, they are nonspecific and suggest mainly ongoing sepsis in general. Detection and assessment of the presence of these biomarkers at the local milieu is an alternate non-invasive option as they are produced at the injury site and increase in anastomotic leaks. If measured serially, can guide to a strong suspicion of a leak before the clinical signs are evident. Methods: Forty-eight patients who underwent intestinal anastomosis for various indications were included. Serial measurement of drain fluid C-reactive protein and procalcitonin were measured on postoperative days 3, 5 and 7. Results: 7 patients developed leaks with two deaths. CRP and procalcitonin levels were higher on all days in comparison with the no leak group. CRP had the highest sensitivity on day 5 with 85.71% and 97.56% specificity on day7. The sensitivity and specificity of procalcitonin were 71.43% and 97.56% on day 5 and day 7. Accuracy was 93.7% for CRP and 87.5% for procalcitonin on the seventh day. Conclusions: Serial analysis of drain fluid CRP and procalcitonin showed persistently increased levels in patients with an anastomotic leak. Correlation of the levels in patients with anastomotic leak suggests the possibility of their utility in the early detection of leaks.